Analysis of the Physical and Inner Structure of the Poetry “Aku Si Pencemburu” and “Pulanglah” Written By Athillahafro Sandi - Irma Suryani; M. Muslim Nasution; Julisah Izar; Yessi Almawa (Jurusan Sejarah, Seni, dan Arkeologi, FKIP, Universitas Jambi, 2021)
Abstract: An analytical study of Athillah Afro Sandi's poem entitled Aku Si Pencemburu and Pulanglah in terms of the physical structure and inner structure was carried out to find out what inner structure and physical structure are contained in the two poems. The research method of this study follows a qualitative descriptive method in which the process and meaning are highlighted in qualitative research. Then the research data were analyzed using the results of poetry analysis before concluding. The results indicate that the poem “Aku Si Pencemburu contains conventional typography, connotative diction, olfactory images, visual images, tactile images, concrete words, personification figure of speech, full rhyme, the theme of jealousy, excessive jealousy, threatening tone, and a message that overly jealous people can harm their partner. Meanwhile,Pulanglah contains conventional typography, the diction of confusion, hopes and requests, tactile and vision images, concrete words, broken rhymes and rhymes with the theme of a place to go home, a sense of hope, a tone of storytelling and pleading, and a message that there will always be a place to go home after traveling so far. Keywords: Poetry; StructurePhysical; Inner Structure; Athillah Afro Sandi